Preliminary assessment of marine phytoplankton distribution and fishing in sri lanka - Yasanthika, W.H.P.; Keerthanaram, T.; Sanjeewani, H.K.N.; Naveendrakumar, G.; Akther, M.S.R. (university of Jaffna, 2020)
Phytoplanktons are the primary producers in marine food webs. The concentration of the chlorophyll-a (Chl-a) shows their abundance among the habitat, estimated by using remote sensing data. Marine fish harvest mainly depends on Chl-a and sea surface temperature (SST) due to food web connectivity. Eight fishing zones of Sri Lanka studied for the average values of Chl-a and SST in 12/24 nmi (nautical miles) shoreline bands in each fishing zone subjected linear regression analysis. Southeast zone in 24 nmi showed the highest average Chl-a (2.54 mg/m3 ), followed by south (2.14 mg/m3 ) and north (1.69 mg/m3 ), while the lowest averages found in the northeast (0.36 mg/m3 ) zone of Sri Lanka. Although results of linear regression suggest preliminary insights for a weak relationship between the fish-catch and Chl-a and SST in Sri Lanka. Southwest zone produces high unit fish-catch of 18.42 Mt/km2 , while the lowest on North (3.90 Mt/km2 ).
Keywords: Chlorophyll-a; Fishing zone; Fish-catch; Sst